Motivated memory in economics: A review - Andrea Amelio; Florian Zimmermann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
In this article, we review the economics literature on the motivated recall of information. Summarizing both theoretical and empirical work, we highlight key results this literature has produced. We also discuss methodological issues when studying motivated memory. We conclude by highlighting open questions and possibly exciting avenues for future research.
Keywords: D01; 330; Memory; Beliefs; Motivated Reasoning; Review